Mediator Intrinsic Motivation dalam Pengaruh Psychological-Capital terhadap Work-Life Balance pada Mahasiswa Aktivis - Feri Indra Irawan; Ila Nurlaila Hidayat (Jurnal Pendidikan (Teori dan Praktik), 2021)
Someone who has several roles in his life, has a challenge to create harmonization in the role, as well as students who are active in some activities. Psychological capital becomes a foundation in facing a challenge, and the presence of a motivation that does not escape in human behavior. The subjects were 58 students of Faculty of Psychology UIN SGD Bandung who are active in some other activities outside the lecture. Correlational quantitative research method is used to find indirect influence of variable IV to DV through mediator variable. Measuring instruments use psychological capital questionnaire (PCQ), work life balance scale, and intrinsic motivation inventory (IMI). The results showed that psychological capital has no significant effect on work life balance directly or indirectly (through mediator). Descriptive analysis results show subjects who have psychological capital of high category 53% and low 47%, on WLB high category 50% and low 50%, and on intrinsic motivation high category 50% and low 50%.